Coping with COVID-19: Strategies of Frontline Nurses - George V. Joy; Jibin Kunjavara; Manoj Kumar Larsen; Rinu J. George (Babali Nursing Research, 2022)
Nurses are the largest workforce within healthcare systems. They are integral to managing pandemics, but due to pandemics, Nurses encounter various traumatic situations, mainly due to distressing and stressful work life. Therefore, nurses must strengthen their resilience in coping with difficulties, adapting to new strategies, and protecting their work and daily life. If nurses have sufficient resilience strategies, burnout and the rate of leaving a job or resigning decrease, posttraumatic growth develops, and work satisfaction increases. The results showed that psychological resilience is an essential predictor of perceived stress in nurses. Protecting the mental health of nursing staff is essential for nurses to combat COVID-19 effectively. Community mental health and psychiatric nurses should develop, implement, and evaluate interventions designed to enhance psychological resilience in clinical nurses.